Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1973
DOI: 10.2136/sssaj1973.03615995003700050044x
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous Coatings on Mineral Surfaces

Abstract: Amorphous coatings on mineral surfaces too thin to be resolved by most electron microscopes were detected bridging particles suspended over holes in the supporting substrates. The coatings are gel‐like in appearance, may flow when wet, shrink and become porous when heated, cement primary particles into large masses, and exhibit a coat‐of‐paint effect with curved solid‐air interfaces. Amorphous gel coatings were found in alumino‐silicate systems, in high aluminum soils, and on quartz surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
2

Year Published

1975
1975
2003
2003

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 0 publications
2
26
0
2
Order By: Relevance
“…From the data of Table 2 it is readily seen that the reduction in AI:Si atom ratio through isomorphous replacement of A1 by Fe is negligibly small. The most reasonable interpretation is one in terms of an excess of silica: whether this is present as a gel coating (Jones and Uehara, 1973) or as discrete particles attached to each kaolinite particle is conjecture. Measurement of the minor element concentration in the kaolinite present in the 0.9-1"0#m fractions of each clay has confirmed the conclusion from M6ss-bauer and ESR measurements (Angel and Hall, 1972;Meads, 1967, 1974) that iron is present as a substituent in the kaolinite structure.…”
Section: Discussionmentioning
confidence: 99%
“…From the data of Table 2 it is readily seen that the reduction in AI:Si atom ratio through isomorphous replacement of A1 by Fe is negligibly small. The most reasonable interpretation is one in terms of an excess of silica: whether this is present as a gel coating (Jones and Uehara, 1973) or as discrete particles attached to each kaolinite particle is conjecture. Measurement of the minor element concentration in the kaolinite present in the 0.9-1"0#m fractions of each clay has confirmed the conclusion from M6ss-bauer and ESR measurements (Angel and Hall, 1972;Meads, 1967, 1974) that iron is present as a substituent in the kaolinite structure.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were prepared by dropping a dilute clay suspension onto Formvar-coated copper grids. Exposure of specimens to the electron beam was held to a minimum to avoid adverse effects of specimen-beam interaction (Jones and Uehara, 1973). DTA analyses of Mg-saturated clays equilibrated at 54% RH were done using a DuPont Model 900 Differential Thermal Analyzer.…”
Section: Methodsmentioning
confidence: 99%
“…This results from the general assumption that noncrystalline materials and reactive components occur only in this fraction, The relatively few studies of the noncrystalline matethe observed differences, however, Follett et al (1965a) and Jones and Uehara (1973) showed that most noncrystalline soil materials exist as coatings that bind aggregates of minerals together, rather than as separate particles. …”
Section: Comparison Of the Noncrystalline Materials Content Of Whole Smentioning
confidence: 99%